Building Financial Institutions in Developing Countries - Reinhard H. Schmidt; Adalbert Winkler (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 1999)
Financial development and financial institution building are important prerequisites for economic growth. However, both the potential and the problems of institution building are still vastly underestimated by those who design and fund institution building projects. The paper first underlines the importance of financial development for economic growth, then describes the main elements of “serious” institution building: the lending technology, the methodological approaches, and the question of internal structure and corporate governance. Finally, it discusses three problems which institution building efforts have to cope with: inappropriate expectations on the part of donor and partner institutions regarding the problems and effects of institution building efforts, the lack of awareness of the importance of governance and ownership issues, and financial regulation that is too restrictive for microfinance operations. All three problems together explain why there are so few successful micro and small business institutions operating worldwide.
urn:nbn:de:hebis:30-18219
Keywords: 330; Corporate Governance; Economic Development; Financial Institution Building; Finanzsektor; Institutionalismus; Corporate Governance; Entwicklungsfinanzierung; Entwicklungsländer